(untitled) (Journal of the College of Education for Women, 2017)
Authentic materials are the most important tools that the teacher could use in class in order to make teaching go smoothly and effectively in transmitting the necessary knowledge to all students. This research has investigated experimentally the effect of using authentic materials in teaching English as a foreign Language, because a number of studies point out that the use of authentic materials is regarded a useful means to motivate learners, arouse their interest and expose them to the real language they will face in real life situations. It is hypothesis that there is no statistical significance difference between the experimental group who taught English as a foreign language by using the authentic materials with those the control group has taught by using the textbook only. The sample of the research is 64 students at College of Physical Education and Science Sport for Women. The groups have exposed to pre and post tests. The experiment has lasted three months. After analyzing the results statistically, they have revealed that there is a significant difference between the two groups in a favour of the experimental one. That is indicated using authentic materials in English foreign teaching is effective